Intelligent system for college selection with analytical hierarchy process method case study approach - Nurhikmah Nurhikmah; Muhammad Ropianto; Novi Hendri Adi (Researcher and Lecturer Society, 2024)
This research aims to develop an innovative decision support system to assist students of SMK Ibnu Sina in selecting universities in Batam City according to their preferences. In order to make the right decision, prospective students must survey information about Batam City universities. With this information, prospective students can assess universities based on accreditation, registration fees, facilities, convenience, and study programs offered to choose the university that best suits their educational needs. The System Development Life Cycle (SDLC) method with a waterfall model is used as a framework to design an effective web-based information system. Data was collected through literature studies and interviews with counseling teachers to establish essential criteria in the college selection process. Based on the results of this analysis, the developed information system includes features such as criteria weighting using the Analytical Hierarchy Process (AHP) method, alternative evaluation, and college ranking. Thus, this SPK is designed to provide accurate and reliable recommendations, expected to increase students' confidence in making decisions regarding colleges that best suit their needs and goals.